KAJIAN LITERATUR: MODEL MENTAL DAN METODE EVALUASINYA - Rian Priyadi; Markus Diantoro; Parno Parno (Pendidikan Kimia Unimus, 2018)
Mental models is an ability that must be possessed by students, so it is necessary to do a meaningful evaluation as a basis for developing students' mental models. However, in Indonesia research on the field of mental models is rarely done because of several factors, one of which is a lack of reference methods that can be used as an evaluation tool. The purpose of this article is to convey methods that can be used to evaluate mental models derived from published articles. The results of our study provide choices of methods that can be used, namely the AC-SMM, SSI, SMD and PDE methods